Detecting self-esteem level and depressive indication due to different parenting style using supervised learning techniques - Al Taawab, Abdullah; Rahman, Mahfuzzur; Islam, Zawadul; Mustari, Nafisa (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.